2023
DOI: 10.3847/2041-8213/acc1e1
|View full text |Cite
|
Sign up to set email alerts
|

JWST Reveals a Population of Ultrared, Flattened Galaxies at 2 ≲ z ≲ 6 Previously Missed by HST

Abstract: With just a month of data, JWST is already transforming our view of the universe, revealing and resolving starlight in unprecedented populations of galaxies. Although “HST-dark” galaxies have previously been detected at long wavelengths, these observations generally suffer from a lack of spatial resolution, which limits our ability to characterize their sizes and morphologies. Here we report on a first view of starlight from a subset of the HST-dark population that is bright with JWST/NIRCam (4.4 μm < 24.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 101 publications
2
20
1
Order By: Relevance
“…However, the first JWST observations challenged this picture. Ferreira et al (2023), Jacobs et al (2023), Nelson et al (2023), andRobertson et al (2023) all found a higher fraction of high-redshift disks and a lower fraction of peculiar galaxies than expected. The initial results, although based on small data sets, suggested either that mergers are less frequent than we thought or that high-redshift disks tend to survive mergers and retain their disk morphology.…”
Section: The Role Of Mergers In Early Galaxy Assemblymentioning
confidence: 58%
See 2 more Smart Citations
“…However, the first JWST observations challenged this picture. Ferreira et al (2023), Jacobs et al (2023), Nelson et al (2023), andRobertson et al (2023) all found a higher fraction of high-redshift disks and a lower fraction of peculiar galaxies than expected. The initial results, although based on small data sets, suggested either that mergers are less frequent than we thought or that high-redshift disks tend to survive mergers and retain their disk morphology.…”
Section: The Role Of Mergers In Early Galaxy Assemblymentioning
confidence: 58%
“…At high redshift, fine structural details are often difficult to recover and in general are ambiguous, hence these questions capture the overall appearance of the source. Our sample is the biggest visually classified sample observed with JWST yet, ∼20 times larger than what is reported in previous JWST morphology results (Ferreira et al 2023;Jacobs et al 2023;Nelson et al 2023). A brief description of each possible resulting class is given below: 1.…”
Section: Visual Classificationmentioning
confidence: 89%
See 1 more Smart Citation
“…The first JWST images revealed a diversity of morphological and structural properties of high-z galaxies (e.g., Ferreira et al 2022;Jacobs et al 2023;Suess et al 2022;Robertson et al 2023b;Kartaltepe et al 2023;Nelson et al 2023), including compact and clumpy structures (e.g., Tacchella et al 2023;Chen et al 2023). GN-z11 is not an exception and the images are morphologically complex because of the haze to the northeast.…”
Section: Resultsmentioning
confidence: 99%
“…Another, perhaps more speculative, explanation for this widespread (and relatively uniform) dust reddening in this (modestly inclined, in contrast to Nelson et al 2023; see also Kokorev et al 2023) galaxy is a dusty wind, as is seen on similar scales in M 82 (e.g., Yamagishi et al 2012;Beirão et al 2015), Mg II absorbers at higher redshifts (Ménard & Fukugita 2012), and also as theoretically expected (e.g., Krumholz & Thompson 2013). To illustrate the plausibility of this explanation, we assume a Milky Way gas-to-dust ratio, for which an A V ∼ 3 corresponds to a hydrogen column density of ∼10 22 cm −2 (Bouchet et al 1985).…”
Section: Morphologies and Structuresmentioning
confidence: 76%